2013
DOI: 10.1186/1471-2296-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician related factors of adherence to evidence based guidelines in diabetes mellitus type 2, cardiovascular disease and prevention: a cross sectional study

Abstract: BackgroundPatients do not always receive guideline-adherent therapy, yet little is known about the underlying causes on the patients’ side. We quantified non-guideline-adherent treatment of chronic diseases (diabetes mellitus, hypertension, cardiovascular disease, heart failure, atrial fibrillation) in primary care and analysed the causes from the physician’s as well as the patient’s view.MethodsWith the intention to analyze the frequency and causes of non-guideline-adherent treatment of patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 20 publications
2
55
0
6
Order By: Relevance
“…Lugtenberg et al studied the causes in three guidelineson red eyes, stroke and thyroid disease. They found that there were different reasons for non-compliance associated with each CPG and, moreover, that clinicians and patients have different views of their non-applicability [14,24]. Berner and Graber comprehensively reviewed the effect of physician over confidence in their own ability as a cause of diagnostic errors.…”
Section: Barriers Identified By Cliniciansmentioning
confidence: 99%
“…Lugtenberg et al studied the causes in three guidelineson red eyes, stroke and thyroid disease. They found that there were different reasons for non-compliance associated with each CPG and, moreover, that clinicians and patients have different views of their non-applicability [14,24]. Berner and Graber comprehensively reviewed the effect of physician over confidence in their own ability as a cause of diagnostic errors.…”
Section: Barriers Identified By Cliniciansmentioning
confidence: 99%
“…35 No presente estudo ainda verificamos que a hipertensão e diabetes estão associadas. Do total de estudos incluídos, em 23% os pacientes possuem ambas as doenças 14,17,19,23,28,34 o que incrementa a complexidade das medidas e, principalmente, do manejo farmacológico, tendo em vista que aumenta a quantidade de fármacos prescritos assim como a necessidade de intensificação das medidas não-farmacológicas.…”
Section: Resultsunclassified
“…Fürthauer et al . found that patients with diabetes with low adherence may not take their medication as prescribed because they accept their symptoms as normal, or may not even notice them . In a review, Lerman cited other possible reasons for low adherence among diabetic patients including lack of social support, poor knowledge about the implications of disease and of not taking medication, substance abuse, and even forgetfulness .…”
Section: Discussionmentioning
confidence: 99%